Development of Learning Media Modules on Material Six Basic Styles Class X TBS 1 at SMK N 1 Sooko Mojokerto - Nararya, Amisarah Jalasena Dwi; Rahayu, Imami Arum Tri; Yuniati, Mita; Arifiana, Deny (Journal of Education Method and Learning Strategy, 2025)
A module is a learning media that is systematically arranged and packaged in the smallest unit that allows students to study independently within a certain time. This study aims to: 1) Describe the feasibility of module learning media on the six basic style material; 2) Describe learning outcomes using module learning media on the six basic style fashion style material. The data collection method in this study used a questionnaire method to measure the feasibility of the media and a test method to measure student learning outcomes. The data analysis method used was to calculate the average value of the module validity level and the assessment of student learning outcomes. The results of the research that has been carried out stated: 1) The development of module learning media on the six basic style material was declared very feasible to be applied to class X TBS 1 at SMK N 1 Sooko Mojokerto with a total average of 3.501; 2) Student learning outcomes after using the module learning media on the six basic style material for class X TBS 1 at SMK N 1 Sooko Mojokerto, the results showed that 90% of students were declared able to meet the classical completion standards, so with this, the module learning media on the six basic style material has been proven to be able to improve student learning outcomes.